2012
DOI: 10.1371/journal.pone.0034684
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Inhibition Is Partially Effective in Attenuating Pre-Existing Immunity against Recombinant Adeno-Associated Viral Vectors

Abstract: Pre-existing immunity against adeno-associated virus (AAV) remains a major challenge facing the clinical use of systemic administration of recombinant AAV vectors for the treatment of genetic and acquired diseases using gene therapy. In this study, we evaluated the potential of bortezomib (marketed under trade name Velcade) to abrogate a pre-existing immunity to AAV in mice, thereby allowing subsequent transduction by a recombinant AAV vector of the same serotype. We demonstrate that bortezomib efficiently red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In addition, the processed vector can also be taken up the professional antigen-presenting cells, which after MHC class II restriction can activate a CD4 + T-cell response (Chen et al, 2006;High, 2012). In line with these observations, the use of proteasomal inhibitors prior to AAV8 administration has shown reduced immune response and increased transduction efficiency in vivo (Karman et al, 2012;Liu et al, 2012). More importantly, K137 is known to be within a previously described MHC class II T-cell recognition epitope (L126-P140) of AAV8 in both humans and mice (Sabatino et al, 2005;Chen et al, 2006).…”
Section: Figmentioning
confidence: 82%
“…In addition, the processed vector can also be taken up the professional antigen-presenting cells, which after MHC class II restriction can activate a CD4 + T-cell response (Chen et al, 2006;High, 2012). In line with these observations, the use of proteasomal inhibitors prior to AAV8 administration has shown reduced immune response and increased transduction efficiency in vivo (Karman et al, 2012;Liu et al, 2012). More importantly, K137 is known to be within a previously described MHC class II T-cell recognition epitope (L126-P140) of AAV8 in both humans and mice (Sabatino et al, 2005;Chen et al, 2006).…”
Section: Figmentioning
confidence: 82%
“…For instance, bortezomib is a US FDA-approved protease inhibitor that targets plasma B cells and is used for treating multiple myeloma. Administration of bortezomib after vector injection has been shown to decrease NAb titer by 8 – 10 folds in naive mice, when compared with mock treatment [85]. This decrease in NAb titer is likely caused by inhibiting antigen processing by the proteasome, which potentially reduces subsequent presentation on B cells and contributes to increased transduction efficiency [8688].…”
Section: The Host Perspectivementioning
confidence: 99%
“…Among the drugs of interest, the clinically approved drug bortezomib seems promising, as it efficiently targets plasma cells 163 while reducing capsid antigen presentation and enhancing AAV vector transduction. 166 In this study, an 8-to 10-fold drop in anti-AAV antibody titer was observed, but the decrease was not sufficient to allow for vector re-administration, and toxicity was observed in some animals. 166 In this study, an 8-to 10-fold drop in anti-AAV antibody titer was observed, but the decrease was not sufficient to allow for vector re-administration, and toxicity was observed in some animals.…”
Section: Transient Immunosuppressionmentioning
confidence: 58%